Dead layer effect and its elimination in ferroelectric thin film with oxide electrodes. (15th June 2016) - Yang, Qiong; Cao, Juexian; Zhou, Yichun; Sun, Lizhong; Lou, Xiaojie
Abstract: Interfacial dead layer effect has been widely noticed in the past and was thought to be responsible for the critical thickness of ferroelectric thin film. Despite extensive studies, the origin is still under fierce debate. The dead layer even exists at the perfect interface without defects and impurities. In this paper, we studied the effects of the electrode/ferroelectric interface on the polarization properties of nano-scale BaTiO3 ferroelectric capacitors by first-principle calculation. A thin layer with reversed polarization is found in the TiO2 -teminated LaNiO3 /BaTiO3 /LaNiO3 capacitor. This pinned domain with reversed polarization at the top interface of ferroelectric film acts as a dead layer and reduces the total polarization. Based on our analyses, this reversed polarization is argued to originate from the intrinsic polarization instability near the top interface of TiO2 -teminated ferroelectric thin film and an interfacial electrical field. An interface modification method has been adopted to remove such dead layer effects. Our results show that a LaXO3 (X = Fe, Co) or YNiO3 (Y = Sr, Ba) buffer layer can effectively remove the dead layer effect in BaTiO3 film. Graphical abstract: